Bremsstrahlung in carbon thick targets by proton incidence - Pérez, Pablo Daniel (2014)
The subtraction of the continuum from an X-ray spectrum emitted by proton bombardment is usually carried out by means of a mathematical fitting. The purpose of the present work is to develop an analytical function to model the continuous spectrum generated in a PIXE experiment for different incident beam energies in carbon thick targets. With this purpose, PIXE spectra of a carbon bulk sample were measured in an ion accelerator. The proton beam energies were varied between 0.7 MeV and 2 MeV and the X-rays generated were collected by an energy dispersive spectrometer. The spectra analysis was performed taking into account the main effects underlying the production of the continuous spectrum. Nevertheless, for the cases considered here, it was found that the atomic bremsstrahlung is the most important and other contributions were neglected. The experimental spectra from carbon thick targets were corrected by self-absorption and detector efficiency. The results show that the spectral shape corresponding to thick targets corrected by these effects is similar to the functional behavior presented by thin targets.